2017
DOI: 10.1002/ppul.23672
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of high fractional exhaled nitric oxide among US youth with asthma

Abstract: High FeNO was observed to be associated with sex, race/Hispanic origin, weight status, tobacco smoke exposure, and abnormal FEV1/FVC, but was not associated with asthma-related respiratory symptoms. These findings may help inform future research and clinical practice guidelines on the use of high FeNO in the assessment of asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
7
1
Order By: Relevance
“…Further studies are needed to determine whether this was simply due to the increase of Hb synthesis caused by hypoxia or related to other factors, such as expression changes of haptoglobin (related to Hb catabolism), which plays an important role in immune regulation and the pulmonary inflammatory response (30). The age, disease course and FeNO levels in the pulmonary function abnormality group were greater than those in the pulmonary function restored group, which is consistent with previous reports (31,32). Kanemitsu et al (33) reported that periostin was an independent risk factor for FEV1 decline.…”
Section: Discussionsupporting
confidence: 86%
“…Further studies are needed to determine whether this was simply due to the increase of Hb synthesis caused by hypoxia or related to other factors, such as expression changes of haptoglobin (related to Hb catabolism), which plays an important role in immune regulation and the pulmonary inflammatory response (30). The age, disease course and FeNO levels in the pulmonary function abnormality group were greater than those in the pulmonary function restored group, which is consistent with previous reports (31,32). Kanemitsu et al (33) reported that periostin was an independent risk factor for FEV1 decline.…”
Section: Discussionsupporting
confidence: 86%
“…Currently, it is known that F E NO values are influenced by age, 5 gender, 5,6 height, 5 atopy, 5,6 smoking, 5,7 respiratory infections, 5 environmental factors, 8 physical activity, 9 and ethnicity. 10 Females have consistently been reported to have lower F E NO levels than men with about 25% lower levels. 5,6 Some of the explanation might reside in differences in height, another known determinant of F E NO, but other differences appear to be exist with regard to gender.…”
Section: Introductionmentioning
confidence: 99%
“…For F E NO to be reliable as a biomarker, it is important to know factors that influence F E NO values. Currently, it is known that F E NO values are influenced by age, gender, height, atopy, smoking, respiratory infections, environmental factors, physical activity, and ethnicity . Females have consistently been reported to have lower F E NO levels than men with about 25% lower levels .…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study in Vietnam found that FeNO in healthy people was not associated with epidemiological factors of the participants such as age, gender, weight, BMI except a fair correlation with height (29). Regarding the relationship between FeNO and genders, Olivieri and colleagues found that there was a difference between the sexes in which women had lower FeNO than men, and this finding was reported in studies (30)(31)(32)(33)(34)(35)(36)(37)(38). On the other hand, many other authors found that this relationship did not exist (29,39,40).…”
Section: Discussionmentioning
confidence: 96%